Intelligence Quotient and Dental Caries - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Dental caries have a detrimental impact on the affected persons, be they children, adolescents, or adults.Aim:To find out the prevalence of dental caries and its relationship with intelligence quotient (IQ) among Southern Saudi Arabian children.Settings and Design:A nonprobability convenience sampling procedure was adopted. Methods: As much as 458 eligible children were selected for the study. Estimation of level of IQ was done by using “Raven's Coloured Progressive Matrices 1998 edition 11.” DMFT/ dmft index was used to assess the prevalence of dental caries among the participants.Statictics used:The collected data were subjected to statistical analysis using Statistical Package for Social Sciences Version 22. Frequencies, percentages, mean, and SDs were applied to report the caries prevalence. Chi-square test and unpaired t-test were applied to test the association between two categorical variables. P valueslessthan 0.05 were considered statistically significant.Results:The prevalence of dental caries was 52.62% with mean total DMFT of 1.48 ± 1.93. Prevalence of primary dmft was 80.13% with mean dmft of 4.60 ± 3.67. The presence of dental caries among primary teeth was statistically significant according to the IQ.Conclusion:The prevalence of dental caries was found to be 52.62% for permanent teeth and 80.13% for primary teeth. The IQ of most children falls under the Grade III category of Raven's Coloured Progressive Matrices grading system. The current study revealed an inversely proportional relationship between IQ grade and the prevalence of dental caries.